2017
DOI: 10.3389/fpsyg.2017.00578
|View full text |Cite
|
Sign up to set email alerts
|

All Tapped Out: Touchscreen Interactivity and Young Children’s Word Learning

Abstract: Touchscreen devices differ from passive screen media in promoting physical interaction with events on the screen. Two studies examined how young children’s screen-directed actions related to self-regulation (Study 1) and word learning (Study 2). In Study 1, 30 2-year-old children’s tapping behaviors during game play were related to their self-regulation, measured using Carlson’s snack task: girls and children with high self-regulation tapped significantly less during instruction portions of an app (including o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 72 publications
2
53
2
Order By: Relevance
“…Specifically, toddlers who have difficulty resisting the impulse to tap the screen indiscriminately may learn more from watching noninteractive video than from using a game or application that requires them to interact with the screen in a prescribed way. Consistent with this hypothesis, toddlers who performed less well on a behavioral inhibition task also tapped more frequently than those with more optimal behavioral inhibition when using a customized word‐learning game on a tablet computer . Additionally, younger preschoolers and boys were less successful than older preschoolers and girls on the behavioral inhibition task.…”
Section: Who Is Most Likely To Benefit From Interactivity?mentioning
confidence: 64%
“…Specifically, toddlers who have difficulty resisting the impulse to tap the screen indiscriminately may learn more from watching noninteractive video than from using a game or application that requires them to interact with the screen in a prescribed way. Consistent with this hypothesis, toddlers who performed less well on a behavioral inhibition task also tapped more frequently than those with more optimal behavioral inhibition when using a customized word‐learning game on a tablet computer . Additionally, younger preschoolers and boys were less successful than older preschoolers and girls on the behavioral inhibition task.…”
Section: Who Is Most Likely To Benefit From Interactivity?mentioning
confidence: 64%
“…In 2 experimental studies, researchers examined children's vocabulary learning using an app compared with nonapp instruction (noninteractive video and picture card instruction) and found no differences in learning. 51,56 In 1 final study, researchers found that children's receptive and expressive vocabulary did not improve after 2 10-minute sessions using a storytelling app with their parents compared with no treatment. 52 Effect sizes for the RCTs, when reported (n = 12, from 3 school-based interventions over 1-9 weeks), ranged from 0.07 to 0.94.…”
Section: La Learningmentioning
confidence: 99%
“…Krcmar and Cingel found that preschoolers showed greater learning from traditional books compared to e-books, with more relevant discourse between parents and children when sharing traditional print books. Moreover, Russo-Johnson et al (2017) found no difference in young children's word learning when images were viewed passively compared to an interactive condition.…”
mentioning
confidence: 74%
“…iPad-based learning has been found to increase student engagement and reduce problem behaviour in both typically and atypically developing populations (El Zein et al 2016;Kucirkova et al 2014). Moreover, touch-screen interactivity allows for more information to be conveyed to the child through touch and motion and for information to be processed as an active experience, which may change how the information is encoded and stored (Russo-Johnson et al 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation